The influence of sequence variations in factor VII, γ-glutamyl carboxylase and vitamin K epoxide reductase complex genes on warfarin dose requirement - Herman, Darja; Peternel, Polona; Stegnar, Mojca; Breskvar, Katja; Dolzan, Vita (Thrombosis and Haemostasis, 2006)
The degree of interpatient variability in the warfarin dose required to achieve the desired anticoagulant response can only partly be explained by polymorphisms in the CYP2C9 gene, suggesting that additional genetic factors such as polymorphisms in genes involved in blood coagulation may influence warfarin dose requirement. In total, 165 Caucasian outpatients on stable maintenance warfarin treatment previously genotyped for CYP2C9 were analysed for common polymorphisms in FVII, GGCX and VKORC1 genes. The -402G>A polymorphism and a variable number of repeats in intron 7 of FVII gene did not significantly influence warfarin dose.The mean warfarin doses increased with the number of (CAA) repeats in the GGCX gene, but the differences were significant only in the CYP2C9*1/*1 subgroup of patients (p=0.032). Common polymorphism (6484C>T) in intron 1 of the VKORC1 gene led to lower warfarin dose requirement; the means were 5.70 (95% C.I. 4.95 - 6.45), 3.49 (3.07 - 3.90) and 2.11 (1.80 - 2.42) mg/day for 6484 CC, CT and TT genotypes, respectively (p<0.001). In contrast, 9041G>A polymorphism in 3’UTR of theVKORC1 gene led to higher warfarin dose requirement; the means were 3.09 (2.58 - 3.60), 4.26 (3.69 - 4.82) and 5.86 (4.53 - 7.19) mg/day for 9041 GG, GA and AA genotypes, respectively (p<0.001).With a regression model we explained 60.0% of variability in warfarin dose, which was due to gene polymorphisms (CYP2C9,VKORC1), age and body-surfacearea. When aiming for individualised warfarin therapy, at least VKORC1 polymorphisms should be included in predictive genotyping besides CYP2C9.
Keywords: Polymorphism; warfarin; cytochrome P450 2C9; pharmacodynamic factors; regression model